Indirect Citation Used In The Development Of Review Of Related Literature Of Final Project: A Case Of Students Of The English Study Program Of Universitas PGRI Semarang - Ngasbun Egar; Niken Ayu (Pascasarjana Universitas Negeri Semarang, 2020)
This study aimed at: 1) finding out the citation forms used in developing review of related literature; and 2) finding out the problems in using indirect citation in developing review of related literature of selected final projects. Analytical qualitative method was used, in which note taking technique was employed to collect the data. The data of the research were taken from final projects written by the students of English study program of Universitas PGRI Semarang. The data was analyzed by identification of the citation forms, and the problems in the use of the indirect citation. The results show that 1) there are two citation forms employed by the writers: integral and nonintegral citations; and 2) there are two dominant problems in the use of indirect citation in developing review of related literature: incomplete sentence, and inconsistency in the use of citation format.